Active travel in Germany and the U.S. Contributions of daily walking and cycling to physical activity. - Buehler, Ralph; Pucher, John; Merom, Dafna; Bauman, Andrian (My University, 2011)
The study estimates differences between Germany and the U.S. over time in population levels of daily walking and cycling at different health-enhancing thresholds across sociodemographic groups. Between 2001/2002 and 2008/2009, the proportion of "any walking" was stable in the U.S. (18.5%) but increased in Germany from 36.5% to 42.3%. The proportion of "any cycling" in the U.S. remained at 1.8% but increased in Germany from 12.1% to 14.1%. In 2008/2009, the proportion of "30 minutes of walking and cycling" in Germany was 21.2% and 7.8%, respectively, compared to 7.7% and 1.0% in the U.S. There is much less variation in active travel among socioeconomic groups in Germany than in the U.S. German women, children, and seniors walk and cycle much more than their counterparts in the U.S.
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Fußgänger; Gesundheitsförderung; Ländervergleich; Fahrradnutzung; Studie; Bewegungsförderung